ANALISIS EFISIENSI PENGUNAAN KAPASITOR BANK TERHADAP PERBAIKAN FAKTOR DAYA DAN JATUH TEGANGAN PADA HOTEL GRAND DAFAM YOGYAKARTA - Lukman Darmawan; Moch. Dhofir; Tri Nurwati (Jurnal Mahasiswa TEUB, 2023)
This research discusses about analysis of the use of capacitor banks for power factor improvement and voltage drop at Grand Dafam Hotel Yogyakarta. For simulation of analysis, researchers used a software called ETAP, Based on the Analysis, The reactive power required at the Grand Dafam Yogyakarta Hotel to improve the power factor to 0.96 is 478.513 kVAR under maximum loadconditions, while on February 24, 2023 it only requires reactive power of 291.92 kVAR. The use of capacitor banks can reduce voltage losses by 1-3% from before the capacitor bank. because the higher the power factor results in a smaller current so that voltage losses will decrease. The total cost of the Grand Dafam Yogyakarta Hotel electricity bill for 1 month before installing the capacitor bank is estimated at Rp35,710,845,732, while after installing the capacitor bank the electricity bill is Rp26,032,673,052 This is because there is no kVARH penalty that has been set according to PLN rules. Keywords : Capacitor Bank, Power Factor, Voltage Drop, Current, Power Loss, Economic Analysis, ETAP